2021
DOI: 10.1002/cam4.3770
|View full text |Cite
|
Sign up to set email alerts
|

Role of surgery in treating epstein‐barr virus‐associated smooth muscle tumor (EBV‐SMT) with central nervous system invasion: A systemic review from 1997 to 2019

Abstract: Epstein-Barr virus-associated smooth muscle tumor (EBV-SMT) is a rare subset of spindle cell tumor. The presence of EBV DNA in smooth muscle tumor was first documented in 1994, and the term EBV-SMT was first described in 1995. 1-4 In the past few decades, patients at any age who were diagnosed with EBV-SMT, have been proved to have a strong correlation with immunodeficiency. 5-8 Cases of EBV-SMTs are most commonly correlated to secondary (or acquired) immunodeficiency, and the cases mainly consisted of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…A systemic review by Chen et al [ 15 ] on EBV-SMT with CNS invasion found that HIV-SMTs have a predilection for the central nervous system. This was seen in our patient with HIV-SMT whose EBV-SMT was found in the thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systemic review by Chen et al [ 15 ] on EBV-SMT with CNS invasion found that HIV-SMTs have a predilection for the central nervous system. This was seen in our patient with HIV-SMT whose EBV-SMT was found in the thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
“…This is also seen in other lymphoproliferative disorders such as PTLD and non-Hodgkin lymphomas in patients with Acquired Immunodeficiency Syndrome (AIDS). Interestingly, Chen et al [ 15 ] notice a concomitant lung and liver involvement in patients with PT-SMT. This was true for two of our patients who had both lung and liver SMTs; one patient with solitary lung involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A greater extent of resection is associated with a survival benefit, particularly in those with intracranial invasion, likely due to the relief of the mass effect or cranial nerve dysfunction. [2] Adjunctive treatment options include radiotherapy, which is more often used in HIV/ AIDS patients, or chemotherapy, which is typically used in postoperative transplant patients. In our case, intravenous antifungal agents were also used for the treatment of CNS cryptococcal infection and cryptococcemia.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to classic smooth muscle tumors, EBV-SMT histology does not correlate well with clinical outcomes. [1] In addition to the roughly 65 cases of central nervous system (CNS) tumors documented in the literature, [2] EBV-SMTs have been described in a variety of anatomic locations, including the liver, lungs, adrenal glands, gastrointestinal tract, and genitourinary organs. [3,4] Opportunistic infections are common in patients with acquired immunodeficiency syndrome (AIDS), but their concomitant incidence with EBV-SMT is not well documented.…”
Section: Introductionmentioning
confidence: 99%